2006
DOI: 10.1097/01.icl.0000178800.40166.25
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Infectious Disease in Corneal Transplant Screening

Abstract: While there are questionnaire identified risk factors associated with seropositivity in this study, their clinical usefulness is unclear. Many factors crucial to the elimination of potentially infectious donor tissues are not identified in the posthumous history typically completed by next of kin. These questionnaires alone do not provide exclusion criteria for elimination of potentially infectious tissues from the donor pool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(36 citation statements)
references
References 14 publications
0
36
0
Order By: Relevance
“…None of the three studies found an association between sex work (including sex bartering or sex for drugs) and HBV. 118,124,125 A study of corneal donors did not find any association between sex work and infection with HBV in univariate analysis. 118 Two studies of psychiatric inpatient veterans did not detect an association between sex bartering 124 or unprotected sex for drugs 125 with HBV infection in multivariate analyses.…”
Section: A Other Illicit Drugs Low-quality Evidence Wasmentioning
confidence: 99%
See 4 more Smart Citations
“…None of the three studies found an association between sex work (including sex bartering or sex for drugs) and HBV. 118,124,125 A study of corneal donors did not find any association between sex work and infection with HBV in univariate analysis. 118 Two studies of psychiatric inpatient veterans did not detect an association between sex bartering 124 or unprotected sex for drugs 125 with HBV infection in multivariate analyses.…”
Section: A Other Illicit Drugs Low-quality Evidence Wasmentioning
confidence: 99%
“…We found very low-quality evidence in one study that did not find an association between cigarette use and HIV (Appendix C) among corneal donors. 118 12. Tattoos and piercing.…”
Section: A Other Illicit Drugs Low-quality Evidence Wasmentioning
confidence: 99%
See 3 more Smart Citations